CAGm: a repository of germline microsatellite variations in the 1000 genomes project. Issue Volume 47:Issue D1(2019) (17th October 2018) - Kinney, Nicholas; Titus-Glover, Kyle; Wren, Jonathan D; Varghese, Robin T; Michalak, Pawel; Liao, Han; Anandakrishnan, Ramu; Pulenthiran, Arichanah; Kang, Lin; Garner, Harold R
Abstract: The human genome harbors an abundance of repetitive DNA; however, its function continues to be debated. Microsatellites—a class of short tandem repeat—are established as an important source of genetic variation. Array length variants are common among microsatellites and affect gene expression; but, efforts to understand the role and diversity of microsatellite variation has been hampered by several challenges. Without adequate depth, both long-read and short-read sequencing may not detect the variants present in a sample; additionally, large sample sizes are needed to reveal the degree of population-level polymorphism. To address these challenges we present the Comparative Analysis of Germline Microsatellites (CAGm): a database of germline microsatellites from 2529 individuals in the 1000 genomes project. A key novelty of CAGm is the ability to aggregate microsatellite variation by population, ethnicity (super population) and gender. The database provides advanced searching for microsatellites embedded in genes and functional elements. All data can be downloaded as Microsoft Excel spreadsheets. Two use-case scenarios are presented to demonstrate its utility: a mononucleotide (A) microsatellite at the BAT-26 locus and a dinucleotide (CA) microsatellite in the coding region of FGFRL1 . CAGm is freely available athttp://www.cagmdb.org/ .